Perlindungan Hukum Preventif dan Represif terhadap Hak Anak dalam Sengketa Hadhanah - Hamdia Hamdia; Muhamad Amin; Juhriati Juhriati (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Post-divorce hadhanah disputes place children in a vulnerable position as two concurrently applicable legal instruments, the Compilation of Islamic Law (KHI) and Law Number 35 of 2014 on Child Protection, operate under paradigmatically different normative logics. This study analyzes the forms of preventive and repressive legal protection of children’s rights in hadhanah disputes according to both instruments using Philipus M. Hadjon’s theory of legal protection. A normative legal research method was employed with statutory and conceptual approaches, analyzed through prescriptive-analytical techniques. The findings indicate that KHI constructs preventive protection through the designation of hadhanah holders based on mumayyiz age categorization, producing normative certainty but not inherently generating substantive protection of the child’s best interests. Law No. 35 of 2014 constructs preventive protection through the adaptive best interest of the child principle, yet lacks operational parameters enabling consistent application in judicial practice. On the repressive dimension, KHI provides a custody transfer mechanism under Article 156(c) tied to a clear forum, but remains reactive-passive as it cannot operate ex officio. Law No. 35 of 2014 positions the state as an active actor through Article 59, yet without operational procedures linking it to the concrete enforcement of hadhanah rulings. Neither instrument has formed an integrated protection system due to the absence of inter-instrument coordination mechanisms during the transitional period between divorce and hadhanah rulings, as well as at the post-judgment enforcement stage.